2018
DOI: 10.1038/s41561-018-0212-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased water-use efficiency and reduced CO2 uptake by plants during droughts at a continental scale

Abstract: Severe droughts in the Northern Hemisphere cause widespread decline of agricultural yield, reduction of forest carbon uptake, and increased CO2 growth rates in the atmosphere. Plants respond to droughts by partially closing their stomata to limit their evaporative water loss, at the expense of carbon uptake by photosynthesis. This trade-off maximizes their water-use efficiency, as measured for many individual plants under laboratory conditions and field experiments. Here we analyze the 13C/12C stable isotope r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
135
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(144 citation statements)
references
References 58 publications
9
135
0
Order By: Relevance
“…Finally, our results show that increased iWUE driven by higher VPD usually corresponds with a reduced GPP (figures 1(e)-(h)), different from increased iWUE under elevated CO 2 that results from increased GPP. Thus, an increase in iWUE does not necessarily translate into increased carbon uptake as simulated by land surface models (Peters et al 2018) or increased tree growth as reported by tree ring data (Lévesque et al 2014, van der Sleen et al 2015, or in other words, whether higher iWUE corresponds to higher GPP depends on the driver of iWUE changes.…”
Section: Excluding the Co 2 Contamination Effectmentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, our results show that increased iWUE driven by higher VPD usually corresponds with a reduced GPP (figures 1(e)-(h)), different from increased iWUE under elevated CO 2 that results from increased GPP. Thus, an increase in iWUE does not necessarily translate into increased carbon uptake as simulated by land surface models (Peters et al 2018) or increased tree growth as reported by tree ring data (Lévesque et al 2014, van der Sleen et al 2015, or in other words, whether higher iWUE corresponds to higher GPP depends on the driver of iWUE changes.…”
Section: Excluding the Co 2 Contamination Effectmentioning
confidence: 98%
“…VPD-effects on iWUE could also partially explain the increasing decoupling of growth and iWUE as observed from tree rings (Andrer-Hayles et al 2011, Peñuelas et al 2011). A VPD-driven increase in iWUE should not increase tree growth, as overall it will likely be accompanied by lower GPP (Peters et al 2018). Finally, our results are relevant for drought monitoring and prediction indices that incorporate information about the difference between potential and actual evapotranspiration (Narasimhan andSrinivasan 2005, Otkin et al 2013), which is largely driven by stomatal conductance during dry periods (Novick et al 2016a).…”
Section: Introductionmentioning
confidence: 98%
“…The expected effect of elevated [CO 2 ] on tree photosynthesis and carbon availability (Huang, Bergeron, Denneler, Berninger, & Tardif, ) may differ across environmental conditions and warming (Lévesque, Siegwolf, Saurer, Eilmann, & Rigling, ; Lindner et al, ; Sarris, Siegwolf, & Kӧrner, ). For instance, a substantial number of studies reported declining long‐term tree growth and productivity (Barber, Juday, & Finney, ; Giguère‐Croteau et al, ; Girardin, Bouriaud, et al, ; Girardin, Hogg, et al, ; Lévesque et al, ; Nock et al, ; Silva & Anand, ) due to regional drought or warming‐induced drought (Liang, Leuschner, Dulamsuren, Wagner, & Hauck, ; Linares & Camarero, ; Peñuelas, Canadell, & Ogaya, ; Peters et al, ; Rahman, Islam, Gebrekirstos, & Bräuning, ). For montane and boreal forests, no growth enhancement related to elevated CO 2 was found (Dawes et al, ; Hättenschwiler, Miglietta, Raschi, & Korner, ; Klein et al, ; Sigurdsson, Medhurst, Wallin, Eggertsson, & Linder, ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a substantial number of studies reported declining long-term tree growth and productivity (Barber, Juday, & Finney, 2000;Giguère-Croteau et al, 2019;Girardin, Bouriaud, et al, 2016;Lévesque et al, 2014;Nock et al, 2011;Silva & Anand, 2013) due to regional drought or warming-induced drought (Liang, Leuschner, Dulamsuren, Wagner, & Hauck, 2016;Linares & Camarero, 2012;Peñuelas, Canadell, & Ogaya, 2011;Peters et al, 2018;Rahman, Islam, Gebrekirstos, & Bräuning, 2019).…”
mentioning
confidence: 99%
“…Respiration is not as well defined with model choice dependent on the spatiotemporal scale under scrutiny [32][33][34]; and 3. Latent heat and water interact at the leaf level via evapotranspiration and hydrological processes in forests [35,36], with research still advancing our knowledge of this complex interaction [37,38].…”
Section: Introductionmentioning
confidence: 99%